2019
DOI: 10.1101/790709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pain-free resting-state functional brain connectivity predicts individual pain sensitivity

Abstract: Individual differences in pain perception are of key interest in basic and clinical research as altered pain sensitivity is both a characteristic and a risk factor for many pain conditions. It is, however, unclear how individual susceptibility to pain is reflected in the pain-free resting-state brain activity and functional connectivity. Here, we identified and validated a network pattern in the pain-free resting-state functional brain connectome that is predictive of interindividual differences in pain sensit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…Analogous to the current findings, a recent study demonstrated that data-driven, multivariate analyses of rsFC in a pain-free state predicted individual differences in pain sensitivity during later testing [84].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Analogous to the current findings, a recent study demonstrated that data-driven, multivariate analyses of rsFC in a pain-free state predicted individual differences in pain sensitivity during later testing [84].…”
Section: Discussionsupporting
confidence: 83%
“…pain anticipation [15,56] and following nociceptive stimulation [64]. Analogous to the current findings, a recent study demonstrated that data-driven, multivariate analyses of rsFC in a pain-free state predicted individual differences in pain sensitivity during later testing [73]. Their measure of pain sensitivity was a ‘composite’ based on a weighted average of heat, cold and mechanical pain thresholds delivered 1-3 days from the time of resting-state functional imaging.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A high degree of correspondence between resting-state and task-related brain activities has been observed in adult fMRI studies 26,27 . In adults, fMRI-recorded resting-state activity is a distinguishing feature of an individual's brain functionality 28 , predicts individuals' task-related brain activity under both experimental 29 and clinical conditions 30 , as well as adults' individual pain sensitivities 31 . While analogous studies have not been conducted in neonatal populations, large-scale resting-state networks are detectable using fMRI from birth and correspond to adult canonical resting-state and task-response networks 32,33 , suggesting a similar functional coupling could exist at this early developmental stage.…”
Section: Introductionmentioning
confidence: 99%